Reproductive Biology of the Rivulated Parrotfish (Scarus rivulatus) in the Seribu Islands: Fecundity, Sex Ratio, Gonadosomatic Index, and Spawning Patterns - Asri Yanti; Sulistiono Sulistiono; Ali Mashar; Nurfajar Nurfajar; Sebastian C..A. Ferse; Ambo Tuwo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Scarus rivulatus is a protogynous hermaphroditic parrotfish closely associated with coral reefs and plays an important ecological role in maintaining reef health through grazing activities. However, information on its reproductive biology in the Seribu Islands, Jakarta, Indonesia, remains limited, although such knowledge is important for sustainable fisheries management. This study aimed to examine the sex ratio, gonadosomatic index (GSI), fecundity, and spawning pattern of S. rivulatus. A total of 2,425 specimens were collected monthly from January to December 2022. Sex identification was based on body coloration and morphology and confirmed by gonadal examination, with individuals classified as female, initial-phase (IP) male, or terminal-phase (TP) male. Total length and body weight were measured, and gonads were analyzed to determine sex, GSI, fecundity, oocyte diameter distribution, and histological characteristics. The overall sex ratio was 1:0.8 (male:female), with females dominating smaller size classes and males occupying larger ones, indicating a protogynous reproductive strategy. GSI values varied throughout the year, with spawning peaks in February, September, and December. Fecundity ranged from 17,013 to 178,813 oocytes and showed positive correlations with total length and body weight. Oocyte diameter distribution and histological observations indicated asynchronous ovarian development, suggesting partial spawning and gradual oocyte release throughout the year. These results highlight the importance of protecting larger individuals and applying seasonal closures and size-based harvesting regulations to maintain population sustainability. This study provides baseline data that can support future management efforts, and further research should explore sex transition processes and larval recruitment dynamics to strengthen ecosystem-based fisheries approaches.